APPLIED SOLAR ENERGY IN THE REDUCTION OF THE POISON OF THE RICINUS COMMUNIS PIE - Cöuras Ford, E. T. L.; Mendes, J. U. L.; Souza, E. M. (Revista de Engenharia Térmica, 2008)
The solar energy was used as a source of heating in Ricinus communis pie with the objective of eliminating or minimizing the percentage of the poison in it, so that it can be used as animal feed. A solar cylinder and plane collector were used as heating system. In the focal area of the solar concentrator a gutter support endowed with stove effect was placed. Parameters that denote the efficiency of the systems for the proposed objective was analyzed.